Life Behavior Assistance Clean and healthy for children, especially students of SMP Negeri No. 2 Tapaktuan Aceh Regency South - Julissasman, Julissasman; T. Cut Lizam; Cut Rahmi (CV. AFDIFAL MAJU BERKAH, 2024)
The implementation of clean and healthy living behavior in schools is still low because there is still a lack of socialization regarding the benefits and risks of not implementing clean and healthy living behavior in everyday life. Due to the low socialization of clean and healthy living behavior, the willingness of students to implement it is also low, which results in disrupted school community health. PHBS is an effort to provide learning experiences for individuals, families, groups, and communities by opening communication channels, providing information, and providing education to improve knowledge, attitudes, and behavior, through a leadership approach (advocacy), fostering an atmosphere (social support), and community empowerment (empowerment) so that they can implement healthy living methods, to maintain, preserve and improve public health (Ministry of Health of the Republic of Indonesia, 2011). Community service in the form of counseling aims to increase students' knowledge of how to increase individual awareness in carrying out clean and healthy daily living behavior in children, especially students of SMP Negeri No. 2 Tapaktuan, South Aceh Regency. The activity method starts with a survey of the counseling location at SMPN 2 Tapaktuan, making counseling materials and implementing counseling. The implementation is before providing education about PHBS, the team of community service lecturers first conducted socialization then gave a pre-test by the community service team and the following stage provided education about PHBS in schools. The results of the pre-test scores from student knowledge with a good category of 20 (50%) and from the implementation of PHBS 25 (62.5%) answered (Yes), and after education, the post-test score for knowledge was 33 (82.5%), the implementation of PHBS 35 (87.5%). This figure is large enough to say that this activity was successful, but there are still students who have not met good scores. And then after the counseling is carried out, this activity will be used as a community service report to carry out the Tridharma of Higher Education. The Community Service Report, in addition to being for publication, is also expected to be a source of information for the target achievement, namely students of SMP Negeri No. 2 Tapaktuan, South Aceh Regency, about implementing clean and healthy living behaviors in everyday life.